2016
DOI: 10.1371/journal.pntd.0005151
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence of Contemporary Dispersal of the Intermediate Snail Host of Schistosoma japonicum: Movement of an NTD Host Is Facilitated by Land Use and Landscape Connectivity

Abstract: BackgroundWhile the dispersal of hosts and vectors—through active or passive movement—is known to facilitate the spread and re-emergence of certain infectious diseases, little is known about the movement ecology of Oncomelania spp., intermediate snail host of the parasite Schistosoma japonicum, and its consequences for the spread of schistosomiasis in East and Southeast Asia. In China, despite intense control programs aimed at preventing schistosomiasis transmission, there is evidence in recent years of re-eme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…As control strategies for the parasite infection in wild animals (e.g., rodents) may not prove logistically feasible or practical, control and removal of the intermediate host snails may be an alternative with the ongoing focus on molluscides and/or environment management. Therefore, our understanding of the genetic characteristics and dispersal potential of O. hupensis in new emerging snail habitats in Taicang of Jiangsu, China may provide a basis for formulating targeted prevention measures, which would exert epidemiological implications for final schistosomiasis elimination across the country [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As control strategies for the parasite infection in wild animals (e.g., rodents) may not prove logistically feasible or practical, control and removal of the intermediate host snails may be an alternative with the ongoing focus on molluscides and/or environment management. Therefore, our understanding of the genetic characteristics and dispersal potential of O. hupensis in new emerging snail habitats in Taicang of Jiangsu, China may provide a basis for formulating targeted prevention measures, which would exert epidemiological implications for final schistosomiasis elimination across the country [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to nucleotide sequences, people with S. japonicum from China, Japan, and Taiwan brought this parasite to Sulawesi, Indonesia (Nelwan, 2022) Human and birds can transmit Sulawesi schistosomiasis japonica distance from an endemic areas. For example, in rare cases, birds may transport ingested snails long distances and secreted alive in a new area (Head et al, 2016). Carney et al reported that a few cases of the disease occur in the Kulawi Valley and the Palu Valley, with individuals in these cases spending considerable time visiting or working in the Lindu Valley (Sudomo and Carney, 1974).…”
Section: Distribution Of Sulawesi Schistosoma Japonicummentioning
confidence: 99%
“…Temperature, turbidity, pH Dengue [75] Temperature Malaria [59,75,87] E. coli, fecal coliform Cholera [45,61,62,81,88] E. coli, fecal coliform, turbidity, pH Dysentery [61,62,89] E. coli, fecal coliform Typhoid fever [61,62] E. coli, fecal coliform, BOD, temperature, DO Cryptosporidiosis [70,81] Fecal coliform Schistosomiasis [76,77,83,85,[90][91][92] E. coli, fecal coliform, temperature, turbidity Buruli ulcer [85] E. coli, fecal coliform, temperature, DO, BOD, TSS, turbidity Hookworm [92] pH = Potential of Hydrogen; DO = Dissolved Oxygen; BOD = Biochemical Oxygen Demand; TSS = Total Dissolved Solid.…”
Section: Water Quality Parameters Diseases Sourcesmentioning
confidence: 99%